Relationship between medical narrative ability and humanistic care quality among oncology nurses (肿瘤科护士叙事护理能力与人文关怀品质的相关性研究) - XIONG Mo (熊沫); HU Luhong (胡露红); KUANG Wan (旷婉); CUI Jinrui (崔金锐); XIAO Huan (肖欢); ZHANG Haiyan (张海燕); GUO Juan (郭娟); LIU Xiaohong (刘小红) (Association of Integrative Nursing, 2022)
Objective To analyze the relationship between medical narrative ability and humanistic care quality among oncology nurses. Methods By convenience sampling method, 192 oncology nurses in Wuhan were selected as survey subjects. The general information questionnaire, Narrative Competence Scale(NCS) of medical staff and the Humanistic Care Quality Scale of nurses were conduct online. Results The average score of NCS of oncology nurses was (148. 18±21. 03) points. The average score of Humanistic Care Quality Scale of oncology nurses was (134. 44±11. 79) points. There was a significant positive correlation between medical narrative ability and humanistic care quality among oncology nurses(r=0. 577). Conclusion The medical narrative ability and the quality of humanistic care of oncology nurses were above the average. The quality of humanistic care of oncology nurses was positively correlated with the level of medical narrative ability. The hospital administrators should pay attention and take actions to improve medical narrative ability, in order to improve the level of humanistic care among oncology nurses. (目的 调查某三级甲等医院肿瘤科护士叙事护理能力、人文关怀品质现状, 并分析两者相关性。方法 选取武汉市某三级甲等医院肿瘤科护士192名为调查对象, 采用一般资料调查表、医护人员叙事能力量表(NCS)、护士人文关怀品质量表进行在线调查。结果 肿瘤科护士叙事护理能力总分(148. 18±21. 03)分, 得分率为78. 40%; 人文关怀品质总分(134. 44±11. 79)分, 得分率为92. 72%。肿瘤科护士的叙事护理能力各维度与人文关怀品质各维度呈正相关(r=0. 577)。结论 肿瘤科护士的叙事护理能力及人文关怀品质处于中上等水平, 两者呈现正相关。护理管理者可以通过提高护士叙事护理能力, 来促进人文关怀品质的提升。)